Determination of Transgene Repeat Formation and Promoter Methylation in Transgenic Plants. (June 2000) - Kumar, Sandeep; Fladung, Matthias
The integration of transgenes into a plant host genome following Agrobacterium tumefaciens -mediated or direct transformation may occur as a single copy or in the form of tandem repeats. The latter has been associated with promoter methylation and silencing of transgenes. Thus, the early screening of such transgenic plants is desirable for ruling out future repeat-dependent transgene instability. We developed a simple PCR-based method in which primer pairs were specifically designed so that amplifications could only be obtained if the transgene was present in the form of multiple inserts in a transgenic line. The method was established using 35S- rolC transgenic aspen lines showing morphologically visible transgenic silencing. Later, it was possible to screen independent transgenic lines showing no visible marker gene expression. Furthermore, a method was developed in which positive PCR amplification was indicative of promoter methylation. The results were consistent and reproducible across different independent transgenic lines. The methods were quick, reliable, consistent and reproducible, and can be useful for routine screening of transgene silencing in lines derived from many different systems.